Water, Human Rights and Governance in the Middle East: An Essay Illustrated by Conflicts over Water Between Israelis and Palestinians - Brooks, David B. (Water Nepal, 2003)
Fresh water has been a contentious issue in countries to the south and east of the Mediterranean Sea since Biblical times. However, the specific issue of human rights to water has received rather little attention, particularly in comparison with both historic and modern attention to legal rights and governance structures. This paper explores this contradiction using, as an example, the Palestinian-Israeli conflict. It goes on to ask whether the absence of an explicit human rights dimension will persist into the future. The paper is labelled an essay because specific references to the literature and direct evidence are not presented at this time. Rather, this paper should be seen as a work in progress, in which a contentious site of conflict over water is used to illustrate some general points. Water Nepal Vol. Vol.9-10, No.1-2, 2003, pp.185-195